2021
DOI: 10.1111/dme.14663
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors associated with repeat diabetic ketoacidosis in people living with type 1 diabetes: A systematic review

Abstract: Aim To systematically review the literature concerning the psychosocial factors associated with repeat diabetic ketoacidosis for people living with type 1 diabetes. Methods PsycInfo, Web of Science, CINAHL, PubMed and ASSIA were searched according to a registered study protocol (PROSPERO CRD42020167381). Data were extracted into a coding spreadsheet, and findings were synthesised narratively. Included papers were also subject to a quality assessment. Results The search yielded 548 unique articles, of which 22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Recurrent admissions for individuals could not be identified in this study but it is likely that some patients contributed more than one AI/AC admission. In the more common endocrine emergency, DKA, clinical experience, together with evidence from a recent meta-analysis, suggests that psychosocial factors appear to account for more frequent hospital presentations in some patients ( 21 – 23 ). In Australia, DKA incidence is highest among 15-19 year old females and, in the young adult age group, there is a female predominance at a ratio of 1·4:1 to males ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrent admissions for individuals could not be identified in this study but it is likely that some patients contributed more than one AI/AC admission. In the more common endocrine emergency, DKA, clinical experience, together with evidence from a recent meta-analysis, suggests that psychosocial factors appear to account for more frequent hospital presentations in some patients ( 21 – 23 ). In Australia, DKA incidence is highest among 15-19 year old females and, in the young adult age group, there is a female predominance at a ratio of 1·4:1 to males ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, DKA incidence is highest among 15-19 year old females and, in the young adult age group, there is a female predominance at a ratio of 1·4:1 to males ( 22 ). DKA is also more common in lower socioeconomic groups ( 21 , 22 ). Overall, about 40% of cases of DKA are thought to be due to non-adherence with the treatment regimen ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with those of previous studies. According to a systematic review, 11 studies have concluded that women were more commonly affected by DKA compared to men, regardless of age, and three studies found the opposite result [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study was the first to note these differences, as no significant evidence is found in other studies. However, many studies have observed that the prevalence of DKA is higher in females than in males [ 21 ]. Another study also suggested that the length of stay for men and women remained the same [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are disparities in occurrence of DKA, in that patients from disadvantaged socioeconomic backgrounds or with poor mental health have a higher incidence rates of DKA ( 7 , 8 ). Although management of diabetes and its associated complications has significantly improved over the past decades ( 9 , 10 ), DKA remains a significant health burden with high morbidity ( 11 ), mortality ( 12 14 ), and relevant utilization of health-care resources ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%